2022
DOI: 10.1093/oso/9780190691288.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Left to Our Own Devices

Abstract: Over the past three decades, digital technologies like smartphones and laptops have transformed the way we work in the United States. Over the same period of time, workers at the top and the bottom of the income ladder have experienced rising levels of job insecurity and anxiety about their economic futures. Despite this connection, we rarely link our everyday technology problems to our economic climate. Left to Our Own Devices explores the ways that workers use their digital technologies to navigate insecure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 7 publications
0
6
0
6
Order By: Relevance
“…As a result, workers that blur the work‐family boundary in ways that extend paid work activities beyond their normal work hours are more likely to be rewarded by the labor platform than workers that maintain a rigid work‐family boundary. Similar role blurring pressures have been observed among platform workers performing domestic and home‐repair services who may have to respond quickly to assignment requests or adjust their schedules to meet their clients' needs and to secure more positive evaluations from them (Ravenelle, 2019; Ticona, 2022).…”
Section: Introductionmentioning
confidence: 78%
“…As a result, workers that blur the work‐family boundary in ways that extend paid work activities beyond their normal work hours are more likely to be rewarded by the labor platform than workers that maintain a rigid work‐family boundary. Similar role blurring pressures have been observed among platform workers performing domestic and home‐repair services who may have to respond quickly to assignment requests or adjust their schedules to meet their clients' needs and to secure more positive evaluations from them (Ravenelle, 2019; Ticona, 2022).…”
Section: Introductionmentioning
confidence: 78%
“…By situating and contextualizing platform workers' work–life choices in relation to previous job histories, the analysis identifies a vicious circle of work–life conflict, as women employees with extensive childcare responsibilities turn to crowdwork platforms in pursuit of increased spatial and temporal flexibility of paid work relative to their previous employers, and to reduce previously experienced conflicts between paid work, home and family in “analogue labor markets”. In the wake of the failed WLB provision by previous employers, platforms become the new inheritors of women's campaigns for WLB (see also Ticona, 2022), and the WLB research agenda needs to respond accordingly. Platforms claim to offer new work–family flexibilities, including spatial flexibility of work, and temporal flexibility of work (including annualized hours, compressed hours and term‐time only working), alongside uncapped emergency leave, and simplified work commutes—and all without the need for any formal application or managerial sign‐off (Table 3).…”
Section: Concluding Discussion: Platforming Work–family Researchmentioning
confidence: 99%
“…In the final section, larger research and theory development possibilities are identified for recentering and advancing work–family research through new engagements with platforms, algorithmic management, and “independent” platform workers. This is in support of feminist activism and campaigning around WLB, and to “understand the unequal terms on which people are included in the digital economy… in the context of already existing sets of social relations” (Ticona, 2022, p. 8).…”
Section: Introductionmentioning
confidence: 99%
“…For example, scholarship on well-compensated technology workers traces the emergence of novel human-software complementarity, such as how algorithmic systems generate new forms of computational and emotional work rather than result in complete job loss (Shestakofsky 2017;Christin 2020). Others study platform-based labor arrangements, emphasizing how complex technological systems intertwine with human efforts while masking such relations on screen (Ravenelle 2019;Rosenblat 2019;Ticona 2022). Some similarly argue for recognition of a hidden "global underclass" underpinning computerized tasks such as content moderation (Gray and Suri 2019;Roberts 2019).…”
Section: Background: Situating Ai and Logistics Workmentioning
confidence: 99%